Systemic cytokine and viral antigen-specific responses in hepatitis D virus RNA positive versus HDV RNA negative patients - Joshi, Shivali S.; Sadler, Matthew; Patel, Nishi H.; Osiowy, Carla; Fonseca, Kevin; Coffin, Carla S. (Frontiers in Medicine, 2023)
Background: Hepatitis B virus (HBV)/Hepatitis D Virus (HDV) co-infection increases the risk of severe liver disease compared to HBV mono-infection. Adaptive immune responses to HDV are weakly detectable, and the involvement of innate immunity in the progression of HDV-related liver fibrosis is suggested. We hypothesize that an overall innate immune activation in HBV/HDV co-infection plays a role in liver disease progression and also impacts virus specific T cell response.Methods: 16 HBV/HDV-co-infected-patients (median age 42y/7F/6Asian/4White/6 Black/15 HBeAg-) and 8 HBV monoinfected-patients (median age 39y/4F/4 Asian/3Black/1White/HBeAg-) with median follow-up of 5 years were enrolled. Liver fibrosis was assessed by liver stiffness measurement (LSM, FibroScan®). Proliferation of CD3+CD4+ T cells in response to viral antigens using CFSE assays and cytokine secreting monocytes was analyzed by flow cytometry.